Pitones Birmanas en Florida del Sur: Soporte Científico para el Manejo de Especies Invasoras - Rebecca G. Harvey; Matthew L. Brien; Michael S. Cherkiss; Michael Dorcas; Mike Rochford; Ray W. Snow; Frank J. Mazzotti; Marianna Domínguez (EDIS)
WEC-242-Span, a 10-page illustrated fact sheet by Rebecca G. Harvey, Matthew L. Brien, Michael S. Cherkiss, Michael Dorcas, Mike Rochford, Ray W. Snow, and Frank J. Mazzotti and translated by Marianna Domínguez, is the Spanish language version of WEC-242, Burmese Pythons in South Florida: Scientific Support for Invasive Species Management. It describes the population of Burmese pythons in south Florida, python reproduction, size and appearance, and the work of the Python Science Support Team. Includes information about how Florida residents can help prevent the spread of invasive snakes, and references. Published by the UF Department of Wildlife Ecology and Conservation, April 2008.